2016
DOI: 10.1098/rsob.160255
|View full text |Cite
|
Sign up to set email alerts
|

An affinity-directed protein missile system for targeted proteolysis

Abstract: The von Hippel–Lindau (VHL) protein serves to recruit the hypoxia-inducible factor alpha (HIF1α) protein under normoxia to the CUL2 E3 ubiquitin ligase for its ubiquitylation and degradation through the proteasome. In this report, we modify VHL to engineer an affinity-directed protein missile (AdPROM) system to direct specific endogenous target proteins for proteolysis in mammalian cells. The proteolytic AdPROM construct harbours a cameloid anti-green fluorescence protein (aGFP) nanobody that is fused to VHL f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 40 publications
1
99
0
1
Order By: Relevance
“…albumin) and the therapeutic target, thus resulting in increased serum half‐lives (Tijink et al ., ; Vosjan et al ., ). In addition, the stability and small size of Nbs make them ideal candidates for targeting intracellular proteins and show great potential as intrabodies (Lobato and Rabbitts, ; Blanco‐Toribio et al ., ; Bouchet et al ., ; Van Impe et al ., ; Bethuyne et al ., ; Fulcher et al ., ; Moutel et al ., ). Other applications of Nbs have been recently reviewed (Bruce et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…albumin) and the therapeutic target, thus resulting in increased serum half‐lives (Tijink et al ., ; Vosjan et al ., ). In addition, the stability and small size of Nbs make them ideal candidates for targeting intracellular proteins and show great potential as intrabodies (Lobato and Rabbitts, ; Blanco‐Toribio et al ., ; Bouchet et al ., ; Van Impe et al ., ; Bethuyne et al ., ; Fulcher et al ., ; Moutel et al ., ). Other applications of Nbs have been recently reviewed (Bruce et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Control and VHL-aGFP. 16 AdPROM cell lines were generated as described previously [22,23], using retroviral-based infections to deliver the AdPROM constructs to the FAM83D GFP/GFP U2OS cells.…”
Section: Generation Of Control and Vhl-agfp16 Adprom Cell Linesmentioning
confidence: 99%
“…This AdPROM system was engineered with the CUL2 substrate receptor VHL tethered to aGFP [12]. The efficacy of this proteolytic AdPROM suggested that this technology could be applied to achieve degradation of endogenous proteins by simply replacing the aGFP with small polypeptide binders that specifically recognize endogenous target proteins.…”
Section: Introductionmentioning
confidence: 99%